Les narradores catalanes del segle XX i XXI: la generació pont - Carles Cortés Orts (Catalonia)
In this paper we will analyse the most recurrent features characterizing the group of Catalan narrators who started their career in the seventies. In our opinion, these writers might represent a bridge generation between those writers who started publishing before the Spanish Civil War and their younger peers who are writing nowadays. First, we will examine a number of theories about the literary generations of the seventies and the eighties, which are likely to reveal those figures that inspired contemporary writers. Then we will make a comparative analysis of several short stories by Carme Riera, M. Antònia Oliver and Isabel-Clara Simó, the most relevant authors of this bridge generation, in order to illustrate the features they share.